Gene Promoter-Methylation Signature as Biomarker to Predict Cisplatin-Radiotherapy Sensitivity in Locally Advanced Cervical Cancer - Contreras-Romero, Carlos; Pérez-Yépez, Eloy-Andrés; Martinez-Gutierrez, Antonio Daniel; Campos-Parra, Alma; Zentella-Dehesa, Alejandro; Jacobo-Herrera, Nadia; López-Camarillo, César; Corredor-Alonso, Guillermo; Martínez-Coronel, Jaime; Rodríguez-Dorantes, Mauricio; de León, David Cantu; Pérez-Plasencia, Carlos (Frontiers in Oncology, 2022)
Despite efforts to promote health policies focused on screening and early detection, cervical cancer 31 continues to be one of the leading causes of mortality in women; in 2020 estimated 30,000 deaths in 32 Latin America were reported for this type of tumor. While the therapies used to treat cervical cancer 33 have excellent results in tumors identified in early stages, those women who are diagnosed in locally 34 advanced and advanced stages show survival rates at five years of less than 50%. Molecular patterns 35 associated with clinical response have been studied in patients who present resistance to treatment; 36 none of them have reached clinical practice. It is therefore necessary to continue analyzing molecular 37 patterns that allow us to identify patients at risk of developing resistance to conventional therapy. In 38 this study we analyzed the global methylation profile of 22 patients diagnosed with locally advanced 39 cervical cancer and validated the genomic results in an independent cohort of 70 patients. We showed 40 that BRD9 promoter region methylation and CTU1 demethylation were associated with a higher 41 overall survival (p = 0.06) and progression-free survival (p = 0.0001); whereas DOCK8 demethylation 42 was associated with therapy-resistant patients and a lower overall survival and progression-free 43 survival (p = 0.025 and p = 0.0001 respectively). These data suggest that methylation of promoter 44 regions in specific genes may provide molecular markers associated with response to treatment in 45 cancer; further investigation is needed.